Christian Ethical Response to Homosexuality: A Theological and Contextual Perspective - Asbanu, Nikodemus (ORTHOTOMEO : Jurnal Penelitian Ilmiah, 2025)
The phenomenon of homosexuality presents significant ethical and theological challenges for the Christian church amid a modern society that is increasingly open to diverse sexual orientations. This study aims to analyze how Christian ethics respond to homosexuality through a theological approach grounded in Scripture and a contextual perspective that considers the current social realities of the church. The research employs a qualitative library method with a theological-ethical approach, utilizing relevant academic literature and biblical sources. The findings indicate that although the Bible explicitly rejects homosexual practices, the church is called to extend love and restoration to those involved. A contextual approach enables the church to uphold moral truth while responding empathetically, inclusively, and pastorally to human struggles. The study concludes that integrating biblical moral principles with contextual understanding provides a foundation for the church’s ethical stance that is just, wise, and relevant in addressing the issue of homosexuality. This research offers practical contributions for churches and theologians in developing an ethical framework that is not only normative but also deeply human and redemptive.